MORPHO-HISTOLOGICAL AND HISTOCHEMICAL STUDY OF THE GALL BLADDER OF WHITE – EARED BULBUL (Pycnonotus leucotis) - Nada Ahmed Al-Shaheen; Adel Jabbar Hussein (Basrah Journal of Veterinary Research)
The present work aims to study the morpho-histological and histochemical structure ofgall bladder in white – eared bulbul (Pycnonotus leucotis) in college of veterinary medicine atuniversity of Basrah. Fifteen samples of adult healthy males were used, which divided in tothree groups. Each group include (5) male used for this study. Tissue sections stained withH&E, Mallory’s, PAS, Verhoeffs and Toluidine- blue. The result indicated that the gallbladder was appear to have blind ovoid- shaped with green color and situated in the middleventral surface of the right lobe of the liver. The histological examination revealed that itconsists of three layers (tunica mucosa, tunica muscularis and tunica serosa or adventitia)